Metacognitive Skills and Academic Performance among Medical Students-An Analytical Cross Sectional Survey - Misbah, Samreen; Mashhadi, Syed Fawad; Urooj, Maryam; Parveen, Musarrat; Aslam, Muhammad Saqlain; Bilal, Muhammad Haris; Shahzad, Fatima; Ullah, Muhammad Anayat (Pakistan Armed Forces Medical Journal, 2024)
Objective: The study objectives were to identify the metacognitive skills in medical students and to find its association with their academic performance.Study Design: Analytical cross-sectional study.Place and Duration of Study: Army Medical College, Rawalpindi Pakistan, from May to Sep 2022.Methodology: MBBS students from second, third and fourth year who had passed their last professional examination were included by convenience sampling. Sample size was calculated using WHO table and keeping 95% confidence level, d=0.05 and p= 0.20. Self-reported questionnaire Metacognitive Awareness Inventory was used to collect online data from 197 students. Hesitant students and incomplete questionnaires were excluded. Data analyzed through SPSS version 26. Mean and standard deviation for descriptive, independent t-test and one-way ANOVA were applied to find differences of mean among different groups (p